Sustainable generation of patient‐led resources in a learning health system - Jennie David; Catalina Berenblum Tobi; Samantha Kennedy; Alexander Jofriet; Madeleine Huwe; Rosa Kelekian; Melissa Neihart; Michelle Spotts; Michael Seid; Peter Margolis; ImproveCareNow Pediatric IBD Learning Health System (Wiley, 2021)
Abstract Background Patient and Family Advisory Councils (PFACs) are an emerging mechanism to integrate patient and family voices into healthcare. One such PFAC is the Patient Advisory Council (PAC) of the ImproveCareNow (ICN) network, a learning health system dedicated to advancing the care of individuals with pediatric inflammatory bowel disease (IBD). Using quality improvement techniques and co‐production, the PAC has made great strides in developing novel patient‐led resources. Methods This paper, written by patients and providers from ICN, reviews current ICN data on PAC‐generated resources, including creation processes and download statistics. Results Looking at different iterations of PAC infrastructure, this paper highlights specific leadership approaches used to increase patient involvement and improve resource creation. Emerging data suggests that the larger ICN learning health system has had limited interactions with these resources. Conclusion ICN provides a novel approach for meaningful integration of patient partners into learning health systems. This paper points to the incredible value of PFAC expertise in the resource creation process. Future work should seek to support PFAC development across other diseases and address the challenges of integrating patient‐led resources into clinical care.